2019
DOI: 10.1097/md.0000000000017543
|View full text |Cite
|
Sign up to set email alerts
|

The investigation of diet recovery after distal gastrectomy

Abstract: This study aims to investigate the adaptation process of the alimentary tract after distal gastrectomy and understand the impact of remnant stomach volume (RSV) on diet recovery.One year after gastrectomy, although patients’ oral intake had increased, the RSV was decreased and small bowel motility was enhanced. Patients with a larger RSV showed no additional benefits regarding nutritional outcomes.We prospectively enrolled patients who underwent distal gastrectomy with Billroth II reconstruction to treat gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…In a previous study, we reported that compared to those with a large GRV, the patients with a small GRV showed no differences in diet habits, volumes, and other nutritional benefits. [9] The average size of the stomach was approximately 600 cc when inflated with gas in a previous study. We measured the average difference between small and large GRVs to be approximately 100 cc, but an average meal of 100 cc is unlikely to affect the patient significantly.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In a previous study, we reported that compared to those with a large GRV, the patients with a small GRV showed no differences in diet habits, volumes, and other nutritional benefits. [9] The average size of the stomach was approximately 600 cc when inflated with gas in a previous study. We measured the average difference between small and large GRVs to be approximately 100 cc, but an average meal of 100 cc is unlikely to affect the patient significantly.…”
Section: Discussionmentioning
confidence: 84%
“…The primary treatment of small gastric remnant syndrome is dietary modification. In a previous study, we reported that compared to those with a large GRV, the patients with a small GRV showed no differences in diet habits, volumes, and other nutritional benefits [9] . The average size of the stomach was approximately 600 cc when inflated with gas in a previous study.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…So far, treatment modalities include surgery, chemotherapy, and radiotherapy, and surgery remains the main and most effective therapy for GC (2). However, GC surgery has caused reduction of food storage volume and various gastrointestinal symptoms, threatening the nutritional status of patients to varying degrees (3)(4)(5). Body weight loss and malnutrition are frequently observed in patients who undergo gastrectomy (6).…”
Section: Introductionmentioning
confidence: 99%
“…Distal subtotal gastrectomy (STG) is a mainstay of treatment for middle and distal-third gastric cancer [ 1 ]. Distal pancreatectomy (DP) with or without splenectomy is currently the gold standard surgical approach for benign and malignant tumors located in the body and tail of the pancreas [ 2 ].…”
Section: Introductionmentioning
confidence: 99%